2020
DOI: 10.1007/s00701-020-04639-5
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and risk factors for postoperative aneurysm residual after microsurgical clipping

Abstract: Objective Aneurysm residuals after clipping are a well-known problem, but the course of aneurysm remnants in follow-up is not well studied. No standards or follow-up guidelines exist for treatment of aneurysm remnants. The aim of this study was to evaluate the risk factors for postoperative aneurysm remnants and their changes during follow-up. Methods We performed a retrospective analysis of 666 aneurysms treated via clipping in our hospital from 2006 to 2016. Postoperative and follow-up angiographic data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Among them, fusiform shape was the one that mainly drew us towards choosing bypass as a rescue strategy in cases of unfeasible clipping reconstruction. Indeed if distal flow could not be preserved with the clipping strategy, trapping and bypass were required [ 17 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, fusiform shape was the one that mainly drew us towards choosing bypass as a rescue strategy in cases of unfeasible clipping reconstruction. Indeed if distal flow could not be preserved with the clipping strategy, trapping and bypass were required [ 17 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…12 Clip ligation is associated with high efficacy and low recurrence rates ranging between 0.26 and 0.53%. 13 Known risk factors for aneurysmal remnants or incomplete clipping are larger aneurysms (11–25 mm), 14 aneurysms other than MCA aneurysms, 14 and atherosclerotic walls of the neck. 15…”
Section: Discussionmentioning
confidence: 99%
“…12 Clip ligation is associated with high efficacy and low recurrence rates ranging between 0.26 and 0.53%. 13 Known risk factors for aneurysmal remnants or incomplete clipping are larger aneurysms (11-25 mm), 14 aneurysms other than MCA aneurysms, 14 and atherosclerotic walls of the neck. 15 A long-term study of 758 aneurysms showed a regrowth risk of 1.83% per year in the case of aneurysmal remnants after incomplete clip ligation.…”
Section: Discussionmentioning
confidence: 99%
“…Achieving complete occlusion in brain aneurysm clipping is crucial from the perspective of rupture and recurrence prevention. Obermueller et al ( 20 ) reported post clipping broad-based remnants are at a higher risk of regrowth. And postoperative regrowth is at a higher risk of rupture of the aneurysm ( 21 ).…”
Section: Discussionmentioning
confidence: 99%